Perancangan Peta Digital Sekolah Menengah Atas dan Kejuruan Negeri di Kota Padang Berbasis Web - Andika Riyadi Jasril; Zulhendra Zulhendra; Denny Kurniadi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
In 2007, Padang city starts the implementation of educational system which refers to the development of Science and Technology by implementing Online Admission System for School (PSB online). This admissions process consists of a fair, transparent, and comprehensive review of all applicants and also can be responsible in accordance with the rule and policy of the Education Department of Padang city. On the website which is provided by the Education Department only publishes the addresses of each school. Therefore, it is need a development system that provides location services of Senior High School and Vocational High School in digital map form. This digital map application designed by using Adobe Flash CS 3 which is presented interactively by combining the element of multimedia such as text, sound, image, animation, and video. By using this digital map, the people and prospective students who want to get in Senior High School or Vocational High School in Padang can find out the school’s geographic location immediately, so that will be easier for the people and students to find out the school’s location that want to be visited .Keyword : PSB online, Digital Map, Multimedia, SMA, SMK and MA State